Examining the Relative Utility of PBIS Implementation Fidelity Scores in Relation to Student Outcomes. (February 2019) - Pas, Elise T.; Johnson, Stacy R.; Debnam, Katrina J.; Hulleman, Chris S.; Bradshaw, Catherine P.
There are several widely used Positive Behavioral Interventions and Supports (PBIS) implementation fidelity measures, including the Schoolwide Evaluation Tool (SET), but there is limited empirical investigation substantiating the association between specific fidelity cut point scores and student outcomes. This article examined different SET cut points in reference to school-level outcomes across 180 elementary, middle, and high schools participating in randomized trials of PBIS. Specifically, we examined the implementation fidelity achieved in the sample, as well as within each school level (i.e., elementary, middle, and high). Using the binary complier index, we examined the association of each of three SET cut points with behavioral and academic outcomes using t tests and receiver operating characteristic (ROC) curve analyses. Although the t tests did not provide confirmation of one specific cut point, post hoc analyses suggested that the cut point may need to be tailored to school levels. There was moderate convergence between implementation on one scale (i.e., responses to behavioral violations) and academic achievement, based on ROC curve analyses for the 70% and 80% cut points. Implications for research and practice are discussed.